Direct Carotid Cavernous Fistula in Infancy: Presentation and Treatment - Rai, Ansaar T.; Sivak-Callcott, Jennifer A.; Larzo, Chris; Marano, Gary D. (American Journal of Neuroradiology, 2004)
Summary: An 11-month-old female patient presented with symptoms of orbital venous congestion. A CT scan showed enlarged superior ophthalmic vein and cavernous sinus on the symptomatic side. Catheter angiography confirmed a direct carotid-cavernous fistula with intra- and extracranial venous drainage. Successful coil embolization of the fistula was performed with resolution of the infant’s symptoms and return of previously elevated intraocular pressures to normal. To our knowledge, no cases of carotid cavernous fistulas in infancy have been previously reported.